Peran Gambar dalam Pembelajaran Kemahiran Membaca Bahasa Arab sebagai Bahasa Asing - Harni Kartika Ningsih; Ikhfy Kanzan Ilahiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The use of deep images in foreign language textbooks is one of the strategies to make it easier to understand vocabulary, grammar, and cultural context visually and intuitively. Bayna Yadaik is one of the Arabic as a foreign language textbook that uses pictures in every part of its reading proficiency. This study aims to explain the role of images in supporting the learning of life topics in the reading proficiency of the book Bayna Yadaik Volume 2. This study uses the analysis of visual texts by Kress & Leeuwen (2006) which focuses on the interactional meaning in visual texts to uncover the interactive meaning of the images. The research method used is descriptive analysis with a qualitative approach. The main data source consists of 26 visual images from Chapters 1-4 of the book Bayna Yadaik Volume 2 in the reading proficiency section. Images in dialogue (12 images) and paragraph text (14 images) support the conversation and situation being discussed and help explain more complex contexts. The results of the analysis showed that images played a role in helping students understand the text and context in the book. Images help understand the text through aspects of social distance, power, contact, and involvement.